2018
DOI: 10.1088/1741-2552/aacbaa
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical basis of the linear electrical receptive fields of retinal ganglion cells

Abstract: This result establishes that the biophysical basis of the electrical receptive field of the linear-nonlinear model is the superposition of transmembrane currents induced by different electrodes at and near the site of action potential initiation. Together with existing experimental support for linear-nonlinear models of electrical stimulation, this provides a firm basis for using this much simplified model to generate more optimal stimulation patterns for retinal implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 59 publications
1
22
0
Order By: Relevance
“…Importantly, the STC analysis revealed that simple STAs, while often correct, had weak amplitudes due to the antagonistic effects of similarly effective cathodic-first and anodic-first biphasic pulses in the STA calculation process. A recent study that similarly examined the eRF can be found in (Esler et al 2018), demonstrating how these methods are being quickly adopted by the research community. Interestingly, this study showed that the types of linear models described here are good approximations for much more complex biophysical models of retinal electrical stimulation.…”
Section: Electrical Noise Stimulationmentioning
confidence: 99%
“…Importantly, the STC analysis revealed that simple STAs, while often correct, had weak amplitudes due to the antagonistic effects of similarly effective cathodic-first and anodic-first biphasic pulses in the STA calculation process. A recent study that similarly examined the eRF can be found in (Esler et al 2018), demonstrating how these methods are being quickly adopted by the research community. Interestingly, this study showed that the types of linear models described here are good approximations for much more complex biophysical models of retinal electrical stimulation.…”
Section: Electrical Noise Stimulationmentioning
confidence: 99%
“…Ex vivo retinal recordings to patterns of multielectrode stimulation have shown that for direct activation of RGCs, electrodes interact linearly during simultaneous stimulation in 90% of RGCs (Jepson et al, 2014a;Maturana et al, 2016). This conclusion is also supported by theoretical studies of multielectrode stimulation of biologically detailed models of RGCs based on morphological reconstruction with Hodgkin-Huxley type dynamics (Esler et al, 2018b). Following this, Maturana et al (2016) showed that a model can accurately predict direct RGC responses to multielectrode stimulation if it is formulated in terms of an electrical receptive fields for each recorded RGC, which describes the contribution each electrode makes to stimulation of that cell in a linear weighted sum.…”
Section: Simultaneous Stimulationmentioning
confidence: 74%
“…1), with the identified axons extending toward the optic disc. Additionally, for each EI, the putative location of the axon initial segment (AIS), a region on the cell considered to be the most sensitive to electrical stimulation (Boiko et al, 2003;Esler et al, 2018b;Fried et al, 2009;Werginz et al, 2020), was assumed to be 13 μm from the soma center in the direction of the nearest axonal electrode, based on previous empirical measurements in the same experimental conditions (Sekirnjak et al, 2008).…”
Section: Resultsmentioning
confidence: 99%